Hubungan Kualitas Pelayanan Kesehatan Anak Dengan Kepuasan Orang Tua di Ruang Rawat Inap RSUD Sukadana Kabupaten Lampung Timur - Mayasari, Ade Tyas; Supriyati, Sri; Ritawati, Ritawati; Rahayu, Sista; Eniwati, Eniwati; Arpiana, Eva (Utan Kayu Publishing, 2021)
The satisfaction felt by the patients is a very important aspect for the image and continuity of a health service take part. In measuring the level of patient satisfaction, there are five dimensions of service quality that are used as assessing factors, namely the dimensions of reliability, responsiveness, assurance, empathy and tangible products. The research objective was to determine the correlation between children’s health services quality with parents’ satisfaction at the inpatient room of the Regional Hospital of Sukadana in East Lampung Regency 2021. The research design used quantitative research with a cross-sectional approach. The population in this research were all parents who received children’s health care at the inpatient room of the regional hospital of Sukadana in East Lampung Regency 2021, which were 45 people while the sample used 45 people. The sampling technique used Total Sampling. The validity analysis in this research used a questionnaire. The results obtained for the dimensions of physical evidence (tangible) p-value = 0.004 less than 0.05, reliability with p-value = 0.003 less than 0.05, responsiveness with p-value = 0.022 less than 0.05, certainty with p-value = 0.000 less than 0.05, empathy with p-value = 0.025 less than 0.05, where it is known that p-value less than 0.05 which means that there is a correlation between the health quality services based on the dimensions of physical evidence, reliability, responsiveness, certainty and empathy with parents’ satisfaction. Suggestions from the regional hospital of Sukadana should make improvements in all dimensions of the quality of health services for children in order to increase patient satisfaction.Abstrak: Kepuasan yang dirasakan oleh pasien merupakan aspek yang sangat penting bagi citra dan kelangsungan suatu tempat pelayanan kesehatan. Dalam mengukur tingkat kepuasan pasien, terdapat lima dimensi kualitas jasa yang digunakan sebagai faktor penilai yaitu yaitu dimensi kehandalan (reliability), daya tanggap (responsiveness), jaminan (assurance), empati (emphaty) dan produk fisik (tangible). Tujuan penelitian ini adalah untuk mengetahui hubungan kualitas pelayanan kesehatan anak dengan kepuasan orang tua di ruang rawat inap RSUD Sukadana Kabupaten Lampung Timur Tahun 2021. Desain penelitian yang digunakan dalam penelitian ini menggunakan penelitian kuantitatif dengan pendekatan cros sectional. Populasi dalam penelitian ini adalah seluruh orang tua yang mendapatkan perawatan pelayanan kesehatan anak di Ruang rawat inap RSUD Sukadana Kabupaten Lampung Timur Tahun 2021 yaitu sebanyak 45 orang sedangkan sampel yang digunakan sebanyak 45 orang Teknik sampling menggunakan Total Sampling. Analisis validitas dalam penelitian ini menggunakan kuisioner. Hasil penelitian yang diperoleh untuk dimensi bukti fisik (tangible) nilai p value = 0,004 kurang dari 0,05, kehandalan (reliability) nilai p value = 0,003 kurang dari 0,05, daya tanggap (responsiveness) nilai p value= 0.022 kurang dari 0.05, kepastian (assurance) nilai p value=0,000 kurang dari 0.05, empati (empathy) nilai p value=0,025 kurang dari 0,05, dimana diketahui pvalue kurang dari 0.05 yang artinya terdapat hubungan antara kualitas pelayanan kesehatan berdasarkan dimensi bukti fisik, kehandalan, daya tanggap, kepastian dan empati dengan kepuasan orang tua. Saran pihak RSUD hendaknya melakukan perbaikan disemua dimensi kualitas pelayanan kesehatan pada anak guna meningkatkan kepuasan pasien.